Opposition Media, State Censorship, and Political Accountability: Evidence from Chavez's Venezuela. (6th September 2021) - Knight, Brian; Tribin, Ana
Abstract: This study investigates the effects of state censorship in the context of the 2007 government closing of RCTV, a popular opposition television channel in Venezuela. Some parts of the country had access to a second opposition channel, Globovision, while other parts completely lost access to opposition television. The first finding, based upon ratings data, is that viewership fell on the progovernment replacement, following the closing of RCTV, but rose on Globovision in areas with access to the signal. Based upon this switching, the paper investigates whether support for Chavez fell in areas that retained access to opposition television, relative to those that completely lost access. Using three measures, Latinbarometer survey data, electoral returns, and data on protest activity, the second finding is that support for Chavez fell in municipalities that retained access to opposition television, relative to municipalities that lost access to opposition television. Taken together, these two findings suggest that voters switching from censored outlets to uncensored outlets can limit the effectiveness of state censorship.